PROSEDUR PENGIKATAN JAMINAN FIDUSIA - , ALEN BASTIYAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The authors devised a thesis with the title of fiduciary registration procedure because the author wanted to know how the procedure and what documents are required to maintaining fiduciary regidtration prosedure. the Government made law No. 42 of 1999 regarding fiduciary guarantee, due to the ever increasing needs of the community. Under the laws of fiduciary guarantee of the items in the assure you with a fiduciary duty to be registered in the registration agency fiduciary guarantee. In addition to the final project report writing,students are required to engage in the practice of field work that aims to make every student can practice the theories that have been obtained at the college into the world of work. The benefits of the practice of fieldwork itself for the writer is to give a daaper understanding of the science ever obtained directly the world of work through the practice of field work. The results of field work practice indicates that low No.42 of 1999 regarding Fiduciary Guarantee, made to give legal certainty to the debtor and the creditor. Fiduciary regristration procedure consists of fiduciary deed: the creation, reading and signing the deed, registration of fiduciary, fiduciary guarantee payment to bank BNI if already registered online, once registered. To meet the requirement of publicity as well as azaz inception fiduciary guarantee.